Pengembangan Media Interaktif Matematika Berbasis Android Dengan Software Ispring Suite Kelas XII - Akhmad Ilmi (Journal Mathematics Education Sigma [JMES], 2023)
Abstract. The purpose of this study is to develop a design and produce an android-based mathematics interactive media with ispring suite software and a pro 2 apk builder website for valid class XII students. This type of research uses research and development (R&D) methods. The model used by the Launer version of the model is the Multimedia Development Life Cycle (MDLC) which has 6 stages, namely concept, design, material collecting, assembly, testing and distribution. Based on the results of the validation test assessment by the media expert team, an average value of 90.77% was obtained with a very decent category and the results of the validation test assessment by the material expert team obtained an average value of 94.27% with a very decent category. So that overall the results of the assessment by media expert validators and materials obtained an average score of 92.52% with categories very feasible to use. Based on the validation test assessment by a team of media experts and a team of material experts, android-based mathematics interactive media with ispring suite software and website 2 apk builder pro for class XII students is very worthy of use in Three Dimension learning. So that the interactive media created can be said to be valid with a little product improvement so that interactive media can be run attractively and effectively.Abstrak. Tujuan dari penelitian ini yaitu mengembangkan desain dan menghasilkan media interaktif matematika berbasis android dengan software ispring suite dan website 2 apk builder pro untuk siswa kelas XII yang valid. Jenis penelitian ini menggunakan metode penelitian dan pengembangan (R&D). Model yang digunakan model versi Launer yaitu Multimedia Development Life Cycle (MDLC) yang memiliki 6 tahapan, yaitu concept, design, material collecting, assembly, testing dan distribution. Berdasarkan hasil penilaian uji validasi oleh tim ahli media diperoleh nilai rerata sebesar 90,77 % dengan kategori sangat layak dan hasil penilaian uji validasi oleh tim ahli materi diperoleh nilai rerata sebesar 94,27 % dengan kategori sangat layak. Sehingga secara keseluruhan hasil penilaian oleh validator ahli media dan materi diperoleh rata-rata skor sebesar 92,52 % dengan kategori sangat layak untuk digunakan. Berdasarkan penilaian uji validasi oleh tim ahli media dan tim ahli materi, media interaktif matematika berbasis android dengan software ispring suite dan website 2 apk builder pro untuk siswa kelas XII sangat layak untuk digunakan dalam pembelajaran Dimensi Tiga. Sehingga media interaktif yang dibuat dapat dikatakan valid dengan sedikit perbaikan produk agar media interaktif dapat dijalankan dengan menarik dan efektif.